Promising reddish-orange light as Eu3+ incorporated in zinc-borosilicate glass derived from the waste glass bottle - Cheong, Wei Mun; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Fen, Yap Wing; Tee, Tan Sin; Loh, Zhi Wei; Hilmi Mayzan, Mohd Zul (Taylor & Francis, 2023)
Eu3+ incorporated zinc-borosilicate glass was synthesized using melt-quenching method. XRD and FTIR verified the amorphous nature of the samples. The absorption spectra indicate the Eu3+ ions in the UV-visible region at ∼394 nm. The direct and indirect band gap decrease from 5.152 eV to 5.082 eV and 4.133 eV to 3.837 eV, respectively. Meanwhile, the refractive index decrease from 2.145 to 2.202, while the Urbach energy ranges from 0.682 eV to 0.733 eV. All the samples have a good transmission percentage at 70–75. Under the excitation of 400 nm, the intensity of the PL spectra increased when the Eu3+ dopant increased. The optimum content for Eu3+ incorporated ZnO–B2O3–GB glass is 3 wt. among the other Eu3+ content (0, 1, and 2 wt.) in this work. The reddish-orange emission at 612 nm (5D0 → 7F2) indicates the most intense emission and the CIE chromaticity coordinates imply in the reddish-orange region.